Analisis Sistem Dan Prosedur Akuntansi dalam Pemberian Kredit Produktif pada PT. Bank Pembangunan Daerah Jambi Cabang Muara Bulian - Fauziah Fauziah; Albetris Albetris (Universitas Batanghari Jambi, 2021)
Know the accounting system and procedures clearly and accurately so that the implementation of credit disbursement is selective and on target, especially productive credit to debtors at PT. Jambi Regional Development Bank Muara Bulian Branch, is the purpose of this research. The implementation of credit disbursement effectively and efficiently can be carried out properly in accordance with the standards and regulations that apply in general and in particular. Comparing the opinions of experts or references that are used as guidelines or technical instructions with the implementation in this research, and describe in detail the chronological details of the results of this research with qualitative descriptive methods. So that clear and detailed results are obtained from this research which shows that the systems and procedures that are run by PT. Jambi Regional Development Bank Muara Bulian Branch in the implementation of lending, especially productive credit, can be carried out properly in accordance with applicable principles and standards. Until the goal is to provide the best service and be able to choose the right debtors so that the provision of productive credit can be carried out effectively and efficiently, as expected.